2017
DOI: 10.1200/jco.2017.35.31_suppl.224
|View full text |Cite
|
Sign up to set email alerts
|

Methadone as the initial long-acting opioid in children with advanced cancer.

Abstract: 224 Background: Methadone is an attractive medication for treating children with advanced cancer who have chronic pain, as it is the only long-acting opioid available as a liquid. This formulation allows for precise dosing that is not possible with the fixed dose of extended release tablets or transdermal patches. Additionally, it can be used in children unable to reliably swallow tablets. Many pediatric oncologists are concerned with methadone’s complex pharmacodynamics and pharmacokinetics, and so it is oft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…13 A dose of 0.2 mg/kg per day was used for methadone as an initial long-acting opioid with reported success in a cohort of 52 pediatric oncology patients. 12 Anghelescu et al reported individualized starting doses ranging from 0.06 to 3.8 mg/kg per day for the treatment of pediatric cancer pain. 15 This range partially reflects high variability in morphine to methadone conversion ratios.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 A dose of 0.2 mg/kg per day was used for methadone as an initial long-acting opioid with reported success in a cohort of 52 pediatric oncology patients. 12 Anghelescu et al reported individualized starting doses ranging from 0.06 to 3.8 mg/kg per day for the treatment of pediatric cancer pain. 15 This range partially reflects high variability in morphine to methadone conversion ratios.…”
Section: Discussionmentioning
confidence: 99%
“…Despite an increased interest in the use of methadone and its potential advantages over other opioids, evidence in pediatric oncology remains sparse, to date consisting only of case reports and case series. 2,11 -16 Both pediatric oncologists 17 and pediatric palliative care physicians 18 have reported a lack of experience with and education in the use of methadone, further justifying the need for additional data regarding the use of methadone in the pediatric oncology setting. Herein, we describe a single institution’s experience with dosing, duration, monitoring, and other clinical considerations for using methadone to treat cancer pain in pediatric EOL care.…”
Section: Introductionmentioning
confidence: 99%
“…Initial median (range) pain intensity was 8 (4-10) and the PPG was 2 (0-4). Irruptive pain was present in 11/62 patients (18%) with a median intensity of 7 (6)(7)(8)(9). Fifty-ve out of 62 patients who initiated methadone (89%) completed the 7-day observation period.…”
Section: Patient Characteristics and Baseline Assessmentsmentioning
confidence: 99%
“…A main concern relates to its variable and erratic half-life and slow elimination phase with the risk of accumulation and delayed toxicity [5,7], requiring cautious initiation and titration. In recent years, some studies began to document methadone´s safety and e cacy as a rst line of treatment for cancer pain in palliative care (PC) patients [8,9]. Still there is limited evidence in relation to the modality of titration and the timing for pain control and dose stabilization [8].…”
Section: Introductionmentioning
confidence: 99%
“…This might allow them to safely administer it to even the very youngest children. 3 Most research on methadone in children for pain is limited to reports on the prolongation of the corrected QT (QTc) interval. 4e6 The use of methadone for pain in children with cancer is limited to a few case series.…”
Section: Introductionmentioning
confidence: 99%